(untitled) (Texas Journal of Medical Science, 2025)
This article explores the capabilities of artificial intelligence (AI) technologies in the field of biomedicine in the context of Uzbekistan in the field of personalized medicine and diagnostics. The article analyzes the importance in early detection of diseases, optimization of treatment and formulation of approaches that meet the individual needs of patients. The benefits of implementation in the healthcare system of Uzbekistan, existing barriers and future prospects will be discussed. The study aims to adapt global experience to local conditions with an emphasis on infrastructure, training and international cooperation. The article presents practical proposals for the use of AI in the modernization of the healthcare system of Uzbekistan